Accelerated Approval of Highly Expensive Disease-modifying Agents: Lessons Learned From the Aducanumab Approval - Santenna Chenchula; Padmavathi R. (Tehran University of Medical Sciences, 2022)
Alzheimer's disease (AD) is a neurodegenerative disease and the most common cause of dementia affecting millions of people yearly. On June 7, 2021, the U.S FDA granted accelerated approval to highly expensive Aducanumab (Aduhelm), the first-ever disease-modifying drug for the treatment of AD based on its efficacy in reducing Amyloid-beta (Aβ) plaques in the brain. A systematic search of the clinical studies available on the newly approved disease modifying AD drug, aducanumab was done. Aducanumab was investigated in two Phase-3 placebo-controlled trials (EMERGE: 1638 and ENGAGE: 1647) for its anti-Alzheimer efficacy, in patients with mild AD or mild cognitive impairment due to AD. Findings from both studies revealed no significant changes between the two groups in both the trials, except in trial EMERGE, in which subjects who had received high-dose aducanumab demonstrated a smaller clinical decline from baseline compared to those treated with placebo i.e., 22 % relative reduction in the Clinical Dementia Rating Scale-Sum of Boxes (CDR-SB) at week 78. Further, nearly 40% of participants showed Amyloid-Related Imaging Abnormalities (35%) (ARIA), including edema and microhaemorrhage (ARIA-E and ARIA-H).Those pharmaceutical agents approved based upon surrogate bio-markers fail to show any clinical efficacy against to symptoms of patients, in spite of high cost and severe adverse events. Therefore any pharmaceutical agents must be approved only based upon evidence from the confirmatory clinical trials. Clinicians also should be vigilant over any newly approved medications over their clinical evidence rather than believing their efficacy and safety based upon decision of approval bodies, especially the drug like aducanumab.